Alpha and Beta amylase activity of Fagopyrum esculentum (Buckwheat): A Medicinal Plant - Prakash, S; Deshwal, S (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Fagopyrum esculentum, common buckwheat popularly known as mithe fapar is one of the staple food crops of the mountain region. Traditionally, it is used to treat constipation and bowel upsets. It is also used by diabetic in different parts of Nepal and India. Due to its high nutritive and medicinal value, medical scientist and researchers are interested in developing this as pharmaceutical plant. In this regard department of biochemistry, College of Applied Education and Health Sciences, C.C.S. University, Meerut, India is working to analyse the biochemical composition and benefits of this plant. So, as a part of a multidimensional project of analyzing various components and their impact on health and diseases, here we are reporting the amylase activity during germination of seed in Buckwheat (Fagopyrum esculentum) plant. Methodology: Common buckwheat (Fagopyrum esculentum) seeds were taken and germinated in dark at room temperature from 0 hours to 192 hours. Biochemical analysis for total amylase, alpha and beta amylase activities was measured by the standard method designed by Bernfeld (1955). Results: The seeds of buckwheat showed high level of amylolytic activity during different stages of germination. At 0 hours, negligible amylase activity was found. The first amylase activity was found at 24 hours and increases up to 96 hours. After 96 hours the total amylase activity starts decreasing and becomes almost negligible at 192 hours. Alpha and Beta –Amylase activity is reported separately. Conclusion: The amylases from the buckwheat showed different level of enzymatic activity during seed germination. Alpha amylase contributed a larger account to total amylase activity. The activity starts increasing and becomes maximum at 96 hours and starts decreasing and becomes lowest at 192 hours suggesting that alpha amylase plays a important role in starch metabolism in developing as well as geminating seeds which can be used for the drug discovery and treatment of several diseases like diabetes, polycystic ovary syndrome, constipation, bowel upsets, obesity and others. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7887 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):53-58